Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2011)
This first special thematic issue of Studies in Second Language Learning and Teaching deals with the learning and teaching of grammar. This seems to be a very fitting topic given the fact that the role of this language subsystem in foreign language pedagogy has never ceased to be a source of considerable controversy and that the teaching of language forms has never been abandoned in the foreign language context. For one thing, even though there is now a broad consensus that teaching formal aspects of the target language is facilitative and may even be indispensable for gaining full mastery of that language, there is much less agreement as to how it should most beneficially proceed. In particular, there are heated debates, often fuelled by staunch allegiance to theoretical positions, concerning the models of grammar that should be adhered to in designing pedagogic intervention, the selection of structures to be taught, the choice of instructional techniques and procedures to be applied, the intensity and timing of instruction, or the nature of the syllabus that should be followed. The contribution of learning and teaching grammar becomes an even more important issue in the foreign language context where the teaching of language forms has always been part and parcel of instruction and the challenge is not to inject elements of focus of form into predominantly communicative activities, but, as Fotos (1998) so aptly put it, to shift the focus from forms to form, by attaching greater importance to meaning and message conveyance in the course of largely code-focused instruction. There is also the crucial question concerning the influence of mediating variables such as individual, linguistic and contextual factors, all of which, most likely in intricate and unpredictable combinations, determine the effects of teachers’ attempts to introduce and practice specific linguistic features and learners’ attempts to master them in terms of explicit and primarily implicit knowledge.